Prevalence of root caries and periodontal conditions in an elderly institutionalized population from Piracicaba - SP (Pesquisa Odontológica Brasileira, 2002)
Preventive and invasive dental procedures have improved in the last two decades, leading to a greater longevity of teeth. As a result, teeth are more susceptible to periodontal diseases and, consequently, to root caries. The purpose of this study was to verify the prevalence of both periodontal diseases and root caries in an institutionalized population from Piracicaba - SP, Brazil. In this study, 151 subjects, aging 54 to 93 years, were examined. The sample was divided into two groups: a group of subjects aging 50 to 75 years and a group of subjects over 75 years old. The sextants were examined and classified as to periodontal health, periodontal treatment needs, prevalence of gingival recession and root lesions. In conclusion, a high prevalence of root caries was verified. That indicates an increase in the susceptibility to these lesions, which is associated with the aging process.